O Programa Bolsa Família em Parintins/AM: estudo com famílias beneficiárias residentes na ocupação Castanhal - Silva, Nancy Maria Farias (Brasil, 2024)
The Bolsa Família Program is one of the income transfer programs of the Brazilian social protection system, which provides cash transfers to individuals and families in situations of socio-economic vulnerability. In this context, this study sought to analyze the social and economic contribution of the Bolsa Família program to the daily lives of families in the Castanhal occupation in Parintins/Am. To answer this objective, we set the following specific objectives. To conceptualize notions of poverty; to contextualize the creation of income transfer programs in Brazil, in particular the Bolsa Familia program; and to identify the social and economic contribution of the Bolsa Familia program to the families of the Castanhal occupation. This is a bibliographical, documentary and field study. The methodological procedures are based on semi structured interviews with the support of data analysis. The results show that the Bolsa Familia program is an income transfer program that makes a significant contribution to the beneficiary families. However, the monetary transfer still faces challenges for the living conditions of individuals, since its resources are still minimal in relation to the multiple needs that families face.